KONSEP DIRI ANAK USIA 7-8 TAHUN YANG MENGALAMI KEKERASAN VERBAL (STUDI KASUS DI JALAN BANGKA 1 D RT 010/RW 013, PELA MAMPANG, JAKARTA SELATAN) - Nevi Rahardyanti; Hapidin Hapidin (STIT Al-Marhalah Al-Ulya Bekasi, 2021)
AbstrackSelf concept formed by what the child perceived to theirself. Every child formed the self concept by theirself to socialized their life. Good self concept will make the child feel proud of theirselfÂ and capable to accepted theirself as well. This study aimed 1) to described the self concept of the child age 7-8 years who suffered verbal abuse 2) to knew the form of verbal abuse had done by parents, 3) to explained the impact of verbal abuse. The method used in this study was Case Study with matching pattern of Campbell as data analysist.Data collection in this study used technique observation, interview and documentation. The results of this study showed that the child have good self concept eventhough they got verbal abuse by their parents, the form of verbal abuse had done by parents who giving bad name-calling, threatening, gave the child indirect critism to hurt the child and the impacts of verbal abuse was the child speak with bad words, the child was easily to cry and the child who had done verbal abuse also had done physical abuse.Â Keywords: Self Concept, Verbal Abuse